Online Gender-Based Violence(GBV) Crime In The Perspective Of Indonesian Criminal Law - Reumi, Frans; Medan, Karolus Kopong; Pelupessy, Ainurrafiqa; Usman, Ramadhan (PT. Anagata Sembagi Education, 2025)
In recent years, developments in information and communication technologies have increased the use of digital media, which has simultaneously expanded the risk of online gender-based violence (GBV). This phenomenon includes sexual harassment, non-consensual dissemination of intimate content, and gender-based threats, which commonly affect women and vulnerable groups. In Indonesia, Law No. 12 of 2022 on the Criminalization of Sexual Violence (UU TPKS) comes as a first step to provide protection to victims, including in cases of online GBV. However, the implementation of the TPKS Law still faces obstacles, such as the lack of understanding of law enforcement officials, difficulties in digital proof, and social stigma against victims. A normative juridical research method was used to evaluate the adequacy of regulations, harmonization of laws, and international best practices. The analysis shows that existing regulations, including the GCV Law, ITE Law, and Criminal Code, still have gaps in effectively addressing online GBV. Legal harmonization, strengthening digital forensic capacity, and increasing gender sensitivity are urgent needs. A holistic approach, including cross-sector collaboration, public education, and policies adaptive to technological developments, is expected to strengthen victim protection. This strategy is needed to realize law enforcement that is responsive, equitable, and supports efforts to eradicate gender-based violence in the digital space.